Input-Output Analysis of Agriculture and Food Sectors in V4 Countries - BARTÓKOVÁ, Ľudmila (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017, 2018)
Input-output analysis represents a useful tool in assessing structural changes in the economy. These tables provide a detailed dissection of intermediate transactions in an economy, and are thereby a means of describing the supply and use of the products of an entire economic system. The aim of this paper is to look closely at the evolution of selected industries, namely agriculture production ( i.e. crop and animal production, hunting and related service activities) and food production ( i.e. manufacture of food products, beverages and tobacco products) in case of V4 countries. We compared the technical, allocation and import coefficients as well as output, input and import multipliers for the period of 2000-2014. We also tried to verify the overall stability of these two industries, the similarities in their development and the strength of their backward and forward linkages.